Aboriginal and Torres Strait Islander family access to continuity of health care services in the first 1000 days of life: a systematic review of the literature - Nina Sivertsen; Olga Anikeeva; Janiene Deverix; Julian Grant (BMC, 2020)
Abstract Background Aboriginal women and their infants experience significant disadvantage in health outcomes compared to their non-Aboriginal counterparts. Access to timely, effective and appropriate maternal and child healthcare can contribute to reducing these existing health disparities. However, accessing mainstream healthcare services often results in high levels of fear and anxiety, and low attendance at subsequent appointments among Aboriginal women, due to inefficient communication, poor service coordination and a lack of continuity of care. Methods This integrative literature review sought to explore factors that contribute to continuity of care and consider service features that contribute to positive care experiences and satisfaction with care received by Aboriginal women and their infants. In total, 28 studies were included in the review and were thematically analysed using Braun and Clarke's six steps of thematic analysis. This was followed by a collaborative, computer-assisted qualitative analysis, which resulted in the emergence of five key themes: lack of continuity of care, impact of lack of continuity of care, continuity of care interventions, impact of continuity of care interventions, and strategies to improve continuity of care. Results Most studies focused on health services in rural or remote Aboriginal communities and there was a lack of documented evidence of continuity of care (or lack thereof) for Aboriginal women living and birthing in regional and metropolitan areas. The majority of studies focused explicitly on continuity of care during the antenatal, birthing and immediate postnatal period, with only two studies considering continuity through to an infant's first 1000 days. Conclusion The review highlights a lack of studies exploring continuity of care for Aboriginal families from the antenatal period through to an infants' first 1000 days of life. Included studies identified a lack of continuity in the antenatal, peri- and postnatal periods in both regional and metropolitan settings. This, along with identified strategies for enhancing continuity, have implications for communities, and healthcare services to provide appropriate and culturally safe care. It also marks an urgent need to incorporate and extend continuity of care and carer through to the first 1000 days for successful maternal and infant health outcomes for Aboriginal peoples.